The Sectoring-Arc Routing Problem (SARP): Models and lower bounds - Nunes, Ana Catarina; Mourão, Maria Cândida (INFORMS 2008 - The Institute for Operations Research and Management Sciences Annual Meeting, 2008)
The Sectoring-Arc Routing Problem (SARP) seeks to partition a mixed graph into a given number of smaller sub-graphs (sectors) and to build a set of trips in each sector, such that the total duration of the trips is minimized. The SARP models activities associated with the streets of large urban areas, such as household waste collection. Linear mixed integer programming models and lower bounds are presented. Computational results over a set of benchmark problems are reported and analyzed.